Aesthetics of aspiration, policies of inclusion: comments to development in two saraus of Rio de Janeiro - Bustos, Diego (2020)
During the last five years and after the days of June, the tradition of the Saraus in Brazil experienced a quantitative change: its incidence increased exponentially throughout the territory of the country, following the example of pioneering events such as Cooperifa. The jump was also qualitative: there is a version of these cultural performances that responds to the new socioeconomic dynamics of the country and that discovers a repertoire of meanings that can be seen as part of a genealogy of development that has always been present behind its staging. The article presents, from the ethnographic work in three of these events, a cultural landscape that interprets the context and meanings of a phenomenon that is not only inscribed in relation to the tradition of the saraus as the space par excellence of peripheral culture, but with the narratives of economic development in the region, especially those put into practice by the governments of the Workers' Party. Commentary and rupture, this new scene of saraus sheds clues about the obstacles still present to the desire for equality of the Brazilian nation.